The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00004770-200207000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Case Selection for Apical Surgery: A Retrospective Evaluation of Associated Factors and Rational

Abstract: Endodontic failures associated with poor quality of endodontics respond favorably to retreatment. Nevertheless, under certain clinical conditions, apicoectomy should be the preferred procedure. A retrospective survey of 200 roots that were referred for apical surgery revealed that 83% of the roots were inadequately obturated, including 8.5% with no root canal filling at all. In 49 of the roots in this group (24.5% of the referred cases) nonsurgical retreatment was judged by an endodontist as either impossible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 12 publications
1
29
0
8
Order By: Relevance
“…They have reported that treatment of 24.5% of the cases was impossible without surgical therapy. [3]…”
Section: Introductionmentioning
confidence: 99%
“…They have reported that treatment of 24.5% of the cases was impossible without surgical therapy. [3]…”
Section: Introductionmentioning
confidence: 99%
“…[172122] In other words, the majority of apical lesions whether cysts or granuloma heal without surgery; only those few lesions that may be true cysts in histology need surgery. [5] Nonsurgical approach in cases of AP is the first treatment option, based on the current concept of treatment decision making;[23] and in case of persistent symptoms the surgical removal of the lesion is considered as the next step. [192022] The treatment outcome for this patient, confirms this statement that although the lesion responded favorably to nonsurgical treatment, the possibility for surgical intervention was kept in mind in case it did not.…”
Section: Discussionmentioning
confidence: 99%
“…failure, and the root canal is coronally accessible and negotiable, surgical treatment is not considered the treatment of choice (8). The success rate for periradicular surgery is lower than that of root canal retreatment.…”
Section: Introductionmentioning
confidence: 99%